Feasibility Platform for Stroke Studies: An Online Tool to Improve Eligibility Criteria for Clinical Trials. Issue 1 (January 2015) - Minnerup, Jens; Trinczek, Benjamin; Storck, Michael; Hohenberger, Maria; Wilpsbäumer, Simon; Abdul-Rahim, Azmil H.; Liesirova, Kai Timo; Broeg-Morvay, Anne; Meisterernst, Julia; Lees, Kennedy R.; Mattle, Heinrich P.; Wersching, Heike; et al.
Abstract : Background and Purpose—: Eligibility criteria are a key factor for the feasibility and validity of clinical trials. We aimed to develop an online tool to assess the potential effect of inclusion and exclusion criteria on the proportion of patients eligible for an acute stroke trial. Methods—: We identified relevant inclusion and exclusion criteria of acute stroke trials. Based on these criteria and using a cohort of 1537 consecutive patients with acute ischemic stroke from 3 stroke centers, we developed a web portal feasibility platform for stroke studies (FePASS) to estimate proportions of eligible patients for acute stroke trials. We applied the FePASS resource to calculate the proportion of patients eligible for 4 recent stroke studies. Results—: Sixty-one eligibility criteria were derived from 30 trials on acute ischemic stroke. FePASS, publicly available athttp://fepass.uni-muenster.de, displays the proportion of patients in percent to assess the effect of varying values of relevant eligibility criteria, for example, age, symptom onset time, National Institutes of Health Stroke Scale, and prestroke modified Rankin Scale, on this proportion. The proportion of eligible patients for 4 recent stroke studies ranged from 2.1% to 11.3%. Slight variations of the inclusion criteria could substantially increase the proportion of eligible patients. Conclusions—: FePASS is an open access online resource to assess the effect of inclusion and exclusion criteria on the proportion of eligible patients for a stroke trial. FePASS can help to design stroke studies, optimize eligibility criteria, and to estimate the potential recruitment rate. Abstract : Supplemental Digital Content is available in the text.